Book Publication Index as a World University Rank Indicator - Koto, J; Widjaya, A.A; Putrawidjaja, M (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
University ranking has indeed become a trend in the world. There are two things behind the growing interest in the use of ranking in the world of higher education they are as a form of accountability and as university strategy to achieve other goals such as prestige, funds, students and also good well known lecturers. This paper proposes Book Publication Index (BPI) as a World University Rank Indicator. In the study, twenty five universities around the world have been taken as case study. The results show that academic staffs of top universities in ASIA and Australia have less interested in writing books. Conversely, academic staffs of top universities in the United States and the United Kingdom have highly an interest in writing books in addition to scientific work. Similarly, Universities in Indonesia focus on publishing books to support their academics.